Pressure-pain thresholds of the plantar foot reflect relative tissue thickness and are systematically higher in active runners than non-runners - Game, Claire; Walsh, Tom; Stevenson, Nathan; Klingler, Werner; Wearing, Scott C. (Frontiers in Physiology, 2025)
BackgroundAthletes have been shown to have greater tolerance and, to a lesser extent, a lower sensitivity to mechanical pain. However, little is known as to whether the pressure-pain sensitivity of the plantar tissues of the foot of runners, which are exposed to repeated, high-impact forces during running, differs to those of non-runners. This study evaluated topographical pressure-pain sensitivity maps of the plantar foot, and at a reference site of the palmar hand, in competitive distance runners and healthy, non-runners and explored the relationship between pressure-pain thresholds and skin and subcutaneous tissue morphology.MethodsMechanical pressure-pain thresholds (PPTs) were measured using an algometer fitted with a cylindrical probe (1 cm2) in 23 competitive distance runners [mean (±SD) age, 39.7 ± 12.0 years; height, 1.75 ± 0.09 m; weight, 68.0 ± 8.4 kg] and an equivalent number of healthy non-runners [mean (±SD) age, 36.6 ± 10.1 years; height, 1.73 ± 0.10 m; weight, 77.6 ± 15.9 kg]. PPTs were determined, bilaterally, using an increasing ramp of ≈30 kPa/s at six standardised sites of the plantar foot, including the centre of the plantar calcaneal area (PCA), the Abductor Hallucis muscle belly (ABH), the plantar metatarsal area of the first (1MH), third (3MH), and fifth (5MH) metatarsal heads, the Abductor Digiti Minimi muscle belly (ADM), as well as the Abductor Pollicis Brevis muscle belly (THE) of the corresponding hand. Skin and subcutaneous tissue thickness at each site was measured using B-mode ultrasound equipped with an 18–4 MHz linear array transducer. Potential differences in PPT values and tissue thickness between groups were assessed using three-way repeated-measures ANOVA and pairwise comparisons with Šidák’s adjustment for multiple comparisons. Relationships between measures of PPT and tissue thickness were explored using nonlinear regression with skin and subcutaneous tissue thickness as the independent variable. Akiake’s Information Criterion was used to assess logit and polynomial fits (linear, quadratic and cubic).ResultsMean PPT values in runners were, on average, 24% higher than those of non-runners, across all sites (F1,43 = 4.6, P = 0.038). Pain sensitivity varied significantly across the plantar surface of the foot in both runners and non-runners (F3.2, 139.9 = 82.5, P <0 .001). PPTs at the PCA were significantly higher (range, 18.6–31.7 kPa) and the ABH significantly lower (range, −31.7 − −6.2 kPa) than those at all other foot sites (P < 0.05). Similarly, mean PPT measured at the THE was significantly lower than that measured at all plantar foot sites (range, −36.9 − −5.1 kPa) in both groups. Runners also presented with significantly thinner tissues than non-runners (F4, 177 = 14.1, P = 0.016) at the PCA [−1.5 mm (−2.8, −0.2), P <0 .05], 1MH [−1.0 mm (−2.0, −0.1), P <0 .05], and ADM [−1.4 mm (−2.6, −0.2), P <0 .05]. The relationship between PPT and tissue thickness was best described by a logit function in runners and non-runners (range R2, 88%–95%). Normalization of pedal PPT values to those of the hand, mitigated the bias in plantar foot PPTs between groups, without altering the shape of the logit function.ConclusionDistance runners presented with lowered sensitivity to mechanical pain than non-runners, despite relatively thinner plantar foot tissues. The topographical variation in PPTs across the plantar foot can be effectively modeled as a function of relative plantar tissue thickness, and the hypoalgesic bias in runners may be mitigated by the normalization of PPT values to those of the hand, without altering the shape of the logit function. Hence, centrally-mediated pathways may underpin the mechanical hypoalgesia of the plantar foot in runners.